Accounting Standards and Financial Market Stability: An Experimental Examination. (24th October 2017) - Lin, Shengle; Pfeiffer, Glenn; Porter, David
Abstract : We examine the effects of three alternative accounting methods in an experimental asset market characterised by bubbles and crashes: fair value (M2M), historical cost (HC) and marked to fundamental value (M2F). Each treatment is replicated under both no‐leverage and leverage conditions. In the no‐leverage condition, we find that accounting methods do not have a significant effect on asset mispricing. In the leverage condition, both M2M and M2F accounting methods exacerbate asset mispricing. Yet, the two differ in leverage dynamics. M2F markets are completely immune to defaults, while M2M markets experience the most frequent and the most severe defaults.